The Migration of the Slovak Population to Békés County – the Problems of the First Immigrants - Franko, Michal (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The study of the history of foreign Slovaks has long been aimed at completing the picture of the condition of those who left their homeland for a better fate in foreign countries. This also applies to Slovak groups in the countries of East-Central Europe, for which the term Lower Land Slovaks has been established. In the present study, we primarily focus on the problems of the first Slovak immigrants who began to settle Békéscsaba (abbreviated Csaba) in 1718. We indicate how the immigrants had to establish themselves almost from the first day in their new home in the new environmental and climatic conditions, how they overcame the difficulties of acquiring subsistence and how they built their new dwellings. The study also deals with the basic issues of health care for the early immigrants, which – from today’s point of view – was at a really low level. Basic questions concerning the education and evangelical faith of the first Slovak immigrants are also the subject of our study.